Akumulasi Logam Berat Zn dan Pb pada Sedimen, Akar dan Daun Mangrove Avicennia alba di Pulau Payung, Sumatera Selatan - Ida Riyanti; Wike Ayu Eka Putri; Tengku Zia Ulqodry; Tiara Santeri (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2019)
Riyanti I, Putri WAE, Ulqodry TZ, Santeri T. 2019. Accumulation of heavy metal Zn and Pb in sediment, root and leaves of mangrove Avicennia alba in Payung Island, South Sumatra. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):141-147. Various industrial activities or natural activity in the Musi River, might contribute to the heavy metals input in mangrove area of Payung Island. The purpose of this study was to analyze the concentration of heavy metals zinc (Zn) and lead (Pb) in sediment, root and leaves of mangrove A. alba. This research was conducted in January 2018. Analysis of heavy metal used Atomic Absorption Spectrophotometry (AAS). The results indicated that Zn concentration of sediment (13.35-22.61 mg/kg) and Pb (0.14-3.17 mg/kg), was still in quality standard level. Zn concentration in roots was 0.45-4.95 mg/kg and in leaf was Zn 2.46-12.76 mg/kg, while Pb on root and leaves was not detected. The value of BCF roots, leaf BCF and TF values were 0.15-0.24 ; 0.30-0.59 ; and 1.69-2.47, respectively. The results of this study indicated that mangrove A. alba in Payung Island as moderate accumulator plants category, and plants could transmit heavy metals effectively.